THE USE OF THE MOTOR DEVELOPMENT SCALE (ROSA NETO, 2002) IN DIFFERENT CONTEXTS OF INTERVENTION AND MOTOR ASSESSMENT (Editora Impacto Científico, 2024)
Motor development is a continuous process that accompanies human beings from childhood to adulthood, resulting from the interaction between biological and environmental factors and the tasks proposed. The literature highlights that this is not just a biological phenomenon, but a dynamic construction influenced by social and cultural experiences. In this context, the Motor Development Scale (EDM), created by Rosa Neto (2002), has become one of the main tools for assessing child motor development in Brazil. The EDM investigates seven areas: fine motor skills, gross motor skills, balance, body schema, spatial organization, temporal organization, and laterality, offering parameters to identify motor delays and support interventions. Studies analyzed demonstrate the applicability of the EDM in special groups, such as children with low vision, Autism Spectrum Disorder (ASD), and Down Syndrome, highlighting its flexibility and effectiveness in different contexts. In addition, the scale is widely used to diagnose deficits and monitor improvements after psychomotor intervention programs and physical activities, confirming its relevance as a pedagogical and clinical tool. It is concluded that the EDM is a robust tool, capable of guiding professionals in promoting motor development and improving children's quality of life.